PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK METERI POKOK AKHLAK TERPUJI KELAS X MIPA 1 MAN 1 KOTA MALANG - Amanatu Rizkiya; Chalimatus Sa’dijah Sa’dijah; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The application of discussion method in the Akidah Akhlak class X MIPA 1 MAN 1 Malang City as well as increasing student learning motivation with the application of the method of discussion in the learning done. This research was conducted as a final assignment in taking the undergraduete level (S1) Islamic Education Study Program, Faculty of Islamic Religion, Islamic University of Malang. This research method uses classrom action research (CAR) by conducting a qualitative research carried out, namely by using the discussion method in the learning subjects Akidah Akhlak class X MIPA 1 MAN 1 Malang City, can increase student learning motivation. The increase in the percentage of learning motivation of student in class X MIPA 1 MAN 1 Malang City significantly increasedstarting from 27.75% in the pre-cycle stage, then increased in the first cycle to 56.71% and increased in the second cycle to 77.93%. This shows that the application of the method of discussion can increase student’s motivation in learning the Akidah Akhlak class X MIPA 1 MAN 1 Malang City.